Efficacy of health ecology-based health education on early rehabilitation outcomes in stroke patients - Zhu, Chengcheng; Zhang, Chengshi; Zhang, Min; Wu, Liwei; Liu, Jia; Liu, Xiaoying; Shang, Min; Zhang, Ting; Kuai, Yingshu (Frontiers in Neurology, 2025)
BackgroundStroke is a leading global cause of disability and mortality in adults, and early rehabilitation is critical for improving patients’ functional recovery and quality of life; however, conventional rehabilitation models often focus solely on medical interventions and overlook the impact of the patient’s comprehensive ecological environment on recovery, making it necessary to explore more holistic intervention approaches. To investigate the efficacy of health ecology theory-based health education in early stroke rehabilitation and its impacts on neurological/motor/cognitive function, psychological status, and metabolic biomarkers.MethodsA total of 150 stroke patients during June–October 2024 were randomized into control and intervention groups based on interventions. Outcomes assessed included National Institutes of Health Stroke Scale (NIHSS) for neurological deficit, Fugl-Meyer Assessment (FMA) for motor function, Modified Barthel Index (MBI) for activities of daily living, Montreal Cognitive Assessment (MoCA) for cognition, Hospital Anxiety and Depression Scale (HADS) for psychological status, and metabolic biomarkers glycated hemoglobin (HbA1c) and low-density lipoprotein cholesterol (LDL-C). Structural equation modeling (SEM) was employed to analyze path relationships among metabolic_indices, recovery_effect, and mental_status.ResultsThe intervention group demonstrated significantly greater improvement in NIHSS, FMA, MoCA, HbA1c, and LDL-C. Multivariate linear regression models showed moderate-to-substantial explanatory power, particularly for LDL-C and HbA1c (adjusted R2 ≈ 30%). Although models for HADS and MBI had lower explanatory power, the intervention effect remained statistically significant (p < 0.05). SEM revealed a significant positive path from mental_status to metabolic_indices (β = 0.42). The negative path from recovery_effect to metabolic_indices (β = −0.45) signified that better recovery correlated with better metabolic profiles. A significant indirect effect of the intervention on metabolic_indices via improved mental_status was identified (β = 1.00 × 0.42).ConclusionHealth ecology-based health education effectively improves neurological/motor/cognitive function and metabolic control during early stroke rehabilitation. The intervention establishes a “physiological-psychological-social” virtuous cycle through multidimensional effects, providing an innovative framework for collaborative stroke recovery management.